When Society Secularizes: Exploring The Transformative Power of Catechesis For Faith Resilience - Agustinus Manfred Habur; Marselina Y. Luju; Adrianus Jebarus (Riviera Publishing, 2026)
This study examines how catechesis can serve as a transformative force for sustaining faith resilience in communities negotiating the pressures of secularization and rapid social change. Drawing on qualitative research conducted in Stasi Rondo Woing, Diocese of Ruteng, Indonesia—a rural Catholic community marked by communal solidarity, dense kinship networks, and limited pastoral infrastructure—the findings reveal that secularizing influences reshape religious participation by shifting priorities and weakening traditional transmission pathways. Yet the social capital embedded in communal and familial life emerges as a critical resource sustaining faith. When catechesis is contextual, dialogical, and rooted in these relational networks, it strengthens believers’ capacity to interpret social change through a faith lens and fosters resilient religious identity. The article argues that catechesis becomes transformative not through doctrinal instruction alone but through its ability to mobilize social capital and embed faith formation within everyday communal life.